Finnish HIV Quality of Care Register (FINHIV). Issue 1 (21st January 2022) - Mutru, Mikaela; Isosomppi, Sanna; Aho, Inka; Liitsola, Kirsi; Brummer-Korvenkontio, Henrikki; Ollgren, Jukka; Luomala, Oskari; Kivelä, Pia
Abstract : Purpose: The Finnish HIV Quality of Care Register (FINHIV) was created to: (1) estimate the number of people living with HIV (PLWH) in Finland, (2) evaluate the national level of antiretroviral medication use and viral suppression, (3) examine the change in the HIV epidemic in Finland to pinpoint issues to address and (4) enable evaluation of the health of the PLWH by combining the FINHIV data with other national healthcare data. Participants: The FINHIV includes all people diagnosed or being treated for HIV infection in Finland since 1984. The register was formed in 2020 by combining data from the National Infectious Diseases Register (information from time of diagnosis, data from 1984) and from the 21 HIV Clinics that treat HIV-positive patients in Finland (earliest data from 1998). The register population forms a nationwide, open cohort with yearly updates; currently it consists of 4218 PLWH (including 718 deceased) with HIV diagnosed or treated in Finland 1984–2019. Current rate of new cases is 150 cases/year. Findings to date: From the FINHIV data, we can confirm that Finland has reached the Joint United Nations Programme for HIV/AIDS (UNAIDS) 90-90-90 targets set for 2020, and that the proportion of virally suppressed is constant between all 21 HIV Clinics in Finland, despite their varying size. Linkage to care is estimated at 94.3% of those diagnosed. In contrast to the treatment results, more than half of the PLWH have been diagnosed at a late stage, and the proportion has increased since 2000. Future plans: Combinations of FINHIV data with other national healthcare register data in Finland will provide further information on other aspects of the health of the PLWH in a high-resource setting (eg, comorbidities, sexual health and use of healthcare resources). Additionally, implementation of patient-reported experience and outcome measures within the FINHIV is ongoing.